Optical conductivity of multifold fermions: The case of RhSi - Maulana, L. Z.; Manna, Kaustuv; Uykur, Ece; Felser, Claudia; Dressel, Martin; Pronin, Artem V (Physical Review Research, 2020)
We measured the reflectivity of the multifold semimetal RhSi in a frequency range from 80 to 20000cm-1 (10 meV-2.5 eV) at temperatures down to 10 K. The optical conductivity, calculated from the reflectivity, is dominated by the free-carrier (Drude) contribution below 1000 cm-1 (120 meV) and by interband transitions at higher frequencies. The temperature-induced changes in the spectra are generally weak: only the Drude bands narrow upon cooling, with an unscreened plasma frequency that is constant with temperature at approximately 1.4 eV, in agreement with a weak temperature dependence of the free-carrier concentration determined by Hall measurements. The interband portion of conductivity exhibits two linear-in-frequency regions below 5000 cm-1 (∼600 meV), a broad flat maximum at around 6000 cm-1 (750 meV), and a further increase starting around 10 000 cm-1 (∼1.2 eV). We assign the linear behavior of the interband conductivity to transitions between the linear bands near the band crossing points. Our findings are in accord with the predictions for the low-energy conductivity behavior in multifold semimetals and with earlier computations based on band structure calculations for RhSi.
CRIS-Team Scopus Importer:2022-04-14